2021
DOI: 10.52827/hititmedj.950527
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and comparison of the seroprevalence of hepatitis B and hepatitis C virus infection in patients admitted to clinics at the Recep Tayyip Erdogan Training and Research Hospital, Turkey

Abstract: Amaç: Somali Mogadişu'daki Türk hastanesine başvuranların hepatit B ve hepatit C seroloji bulgularını değerlendirmeyi ve mevcut prevalansının belirlenmesi.Gereç ve Yöntemler: Hastaların demografik bulguları ve hepatit test sonuçları (HBsAg, anti-HBs antikoru ve anti-HCV) dosyalarından geriye dönük olarak kaydedildi.Bulgular: Çalışmamıza yaş ortalaması 34 (31/61) yıl olan 75.903 (%49,8) erkek ve 76.363 (%50,2) kadın olmak üzere toplam 152.266 hasta dahil edildi. Anti-HCV için test edilen 67.749 hastanın 1.278'i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In a previous study conducted in our hospital and covering a two and a half year period (2017-2019), HBsAg seroprevalence was found to be 8.2% [10]. In the same study, anti-HBs seroprevalence was found to be 32.2% and anti-HCV seroprevalence was found to be the second most common cancer in men in Somalia, while the incidence of liver cancer was twice as high in men as in women [16].…”
Section: Discussionmentioning
confidence: 62%
“…In a previous study conducted in our hospital and covering a two and a half year period (2017-2019), HBsAg seroprevalence was found to be 8.2% [10]. In the same study, anti-HBs seroprevalence was found to be 32.2% and anti-HCV seroprevalence was found to be the second most common cancer in men in Somalia, while the incidence of liver cancer was twice as high in men as in women [16].…”
Section: Discussionmentioning
confidence: 62%